Projeto e desenvolvimento de um controlador de carga/descarga de baterias para sistemas fotovoltaicos - Geraldi, Marcelo Theis (2018)
In this paper the design and development of a digital controller for photovoltaic systems using the Arduino UNO (ATMEGA328P microcontroller) is performed, in order to control and monitoring more effectively the charge/discharge process of lead-acid batteries, which are widely used in photovoltaic systems. Through of techniques and control strategies known and already applied in several similar products in the market, such as the State Of Charge (SOC) and battery charging by Pulse Width Modulation (PWM), applying control and monitoring algorithms, protection systems and signs/indications of information through LEDs and an LCD display, has been adopted in the developed device, making the process of charging/discharging the batteries more intuitive and considered appropriate. The digital controller, after several tests and graphs, resulted in effective charging process of the lead-acid battery, with only a few variations observed, which are result of the variations caused by the solar panel and loads applied in the system (USB and terminals), however, these are considered acceptable situations. Although the digital controller fulfills its main objective, offering a good performance in the process of charging the lead-acid batteries, there are still several interesting improvements to be applied in the device, such as the use of more sophisticated and complex methods (MPPT, for example ), range of support for batteries of smaller capacity, current sensing, among others.